State of the union, 1994 : the Clinton administration and the nation in profile - Caplan, Richard (Richard D.); Feffer, John (Routledge, 2019)
State of the Union 1994 assesses the Clinton administration's first year in office and lays out progressive policy alternatives in the realms of foreign and domestic affairs. It charts the course of the nation in fourteen critical areas, giving readers a solid basis of information on which to compare trends historically and internationally and to m